A study of diabetes associated oral manifestations - T Shanmugam Kathiresan; K. M. K Masthan; R Sarangarajan; N Aravindha Babu; Prashant Kumar (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this work was to determine the frequency of oral changes in diabetic patients and to study the relationship between periodontal disease and diabetes mellitus. Materials and Methods: The study sample consisted of 440 known diabetic patients between the age group of 20-80 years, of which 212 were males and 228 were females. One hundred and six patients were below 40 years, 138 patients between 41 and 50 years, 97 in 51-60 years, and 99 above 60 years of age. Data were statistically analyzed by Student's t-test. Results: Nearly 57% of the patients showed a Russell's Periodontal Index score of 2-4.9, which suggested an established periodontal disease. Risk factors for the people above the age of 40 years to develop diabetes were 76%. Conclusion: The frequency of oral manifestations in diabetic patients was significantly high, hence showing a relationship of gingival and periodontal diseases with diabetes mellitus.